2018
DOI: 10.4103/jos.jos_44_18
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malocclusion and orthodontic treatment need in Omani adolescent population

Abstract: OBJECTIVE:To determine the prevalence of malocclusion and orthodontic treatment need in a sample of Omani adolescents aged 11–16 years.MATERIALS AND METHODS:The total sample included 854 adolescents with 387 boys and 467 girls between the age of 11 and 16 years with no previous orthodontic treatment history. The study design was cross-sectional. The parameters studied were skeletal relationship, lip competency, teeth impactions, missing teeth, contact point displacement, crowding, spacing, incisors and molars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 30 publications
5
10
0
1
Order By: Relevance
“…4.5% of the subjects who took part in the study in North Cyprus exhibited the prevalence of Angles Class III malocclusion. Similar results were obtained in a study conducted in Oman [3] in which 4.2% of the subjects exhibited prevalence of Angles Class III malocclusion. Furthermore, 4.3% of the subjects in Italy [35], 6.1% of the subjects in Iran [2], 0.1% of the subjects in India [40] exhibited prevalence of Angles Class III malocclusion.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…4.5% of the subjects who took part in the study in North Cyprus exhibited the prevalence of Angles Class III malocclusion. Similar results were obtained in a study conducted in Oman [3] in which 4.2% of the subjects exhibited prevalence of Angles Class III malocclusion. Furthermore, 4.3% of the subjects in Italy [35], 6.1% of the subjects in Iran [2], 0.1% of the subjects in India [40] exhibited prevalence of Angles Class III malocclusion.…”
Section: Discussionsupporting
confidence: 89%
“…As the name implies, ICON is an index designed to assess not only treatment difficulties, ICON is also evaluates treatment outcomes and treatment needs. ICON was developed as an international index based on the common opinion of the 97 orthodontists from 9 countries, including America and 8 European countries by Daniels and Richmond in 2000. ICON index, a new orthodontic occlusal index, is said to replace IOTN [3], PAR [4] (Peer Assessment Rating and Dental Aesthetic Index) in recent years. [29,24,19,27,32,41,33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The NNOT prevalence found in the present study was higher than that reported in various other countries (IOTN-DHC≥4). A 1-55% NNOT prevalence is reported for countries in Asia [24][25][26][27][28][29], while 17-36% was observed in Europe [30][31][32] and 25-78% in America [13][14][15]33].…”
Section: Discussionmentioning
confidence: 99%
“…La distribución de los pacientes por tipo de maloclusion encontrada (según los criterios de Angle) es concordante con lo reportado por otros autores como Beckwith et al (1999), Burgos (2014) y Al Jadidi et al (2018), aunque la maloclusion de Clase III encontrada es menor a otros estudios, lo que se explica probablemente porque los casos complejos de resolucion quirurgica no se atienden en el CESFAM.…”
Section: Discussionunclassified